2019
DOI: 10.22437/jmk.v8i3.8596
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Faktor-Faktor Yang Mempengaruhi Keberhasilan Berwirausaha Industri Percetakan (Studi Kasus Wirausaha Industri Percetakan Di Kota Jambi)

Abstract: ABSTRACT This study aims to determine the factors that influence the success of the Printing Industry business in Jambi City. The population in this study was the printing industry entrepreneur with 55 respondents. Sample collection was carried out by distributing questionnaires with census techniques to 55 entrepreneurs who already have a printing industry in the city of Jambi. This research uses Multiple Linear Regression analysis tools. The results showed that the factors that had a significant influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
1
0
1
Order By: Relevance
“…It is consistent with the theory of opportunity identification and development developed by Ardichvili et al (2003) that the greater the number of opportunities, the higher the probability of success. The results of this study are also in line with the results of research conducted (Lee and Yang (2013), (Limsong et al 2017), andHermansyah andDahmiri (2020) that the opportunity variable is the primary driver of success and opportunity has a positive effect on business results.…”
Section: The Effect Of Opportunity On Successsupporting
confidence: 90%
See 1 more Smart Citation
“…It is consistent with the theory of opportunity identification and development developed by Ardichvili et al (2003) that the greater the number of opportunities, the higher the probability of success. The results of this study are also in line with the results of research conducted (Lee and Yang (2013), (Limsong et al 2017), andHermansyah andDahmiri (2020) that the opportunity variable is the primary driver of success and opportunity has a positive effect on business results.…”
Section: The Effect Of Opportunity On Successsupporting
confidence: 90%
“…The examination results directed by Lee and Yang, 2013) and Limsong et al (2017) on the chance variable show that chance is the essential driver of business achievement. Besides, the most recent exploration directed by Hermansyah and Dahmiri (2020) found that possibilities emphatically influence business results. Therefore, as needs are, considering the discussion above, we hypothesize that opportunity positively affects the success of aṣnāf entrepreneurs (H2).…”
Section: Shanementioning
confidence: 99%
“…Banyak sekali berbagai jenis dan teknik cetak yang digunakan oleh para usaha percetakan mulai dari yang sederhana hingga yang canggih karena teknologi cetak mengalami perkembangan yang signifikan sesuai dengan zamannya. Desain grafis, sablon dan percetakan merupakan salah satu bentuk usaha yang menjanjikan yang dapat memberikan peluang dan keuntungan bagi masyarakat, terutama saat adanya pemilihan kepala daerah (Hermansyah & Dahmiri, 2019: Rini et al, 2020: Sukma et al, 2022.…”
Section: Pendahuluanunclassified
“…Hasil temuan penelitian Nuryatimah & Dahmiri (2021) menunjukkan bahwa kompetensi SDM berpengaruh positif terhadap keberhasilan usaha. Namun, temuan penelitian Hermansyah & Dahmiri (2019) menyatakan hal yang berbeda, kompetensi SDM tidak memiliki pengaruh positif terhadap keberhasilan usaha.…”
Section: Pendahuluanunclassified
“…Hasil penelitian Dewi (2022) menunjukkan adanya hubungan positif antara kompetensi dengan keberhasilan usaha, yang mengindikasikan bahwa semakin baik kompetensi SDM, maka potensi keberhasilan usaha akan meningkat. Namun, penelitian Hermansyah & Dahmiri (2019) menemukan hasil yang berbeda, yaitu tidak ada hubungan negatif antara kompetensi SDM terhadap keberhasilan usaha.…”
Section: Kompetensi Sdm Penggunaan Informasi Dan Keberhasilan Usahaunclassified